Analysis of municipal water use in urban regions across the contiguous United States - Dezfooli, Donya, author; Arabi, Mazdak, advisor; Sharvelle, Sybil, committee member; Carter, Ellison, committee member; Goemans, Christopher G., committee member (Colorado State University. Libraries, 2024)
Urban water use in the United States faces increasing social and environmental pressures. Challenges such as population growth, urbanization, extreme weather events, and climate change threaten the balance between water supply and demand, jeopardizing access to safe and reliable drinking water for city dwellers. Additionally, the traditional linear "take-make-waste" approach, once common in addressing water-related issues, has proven unsustainable due to its reliance on finite energy and resources. Therefore, it is imperative to shift from this linear model to a more integrated and sustainable approach, known as "One Water". This shift requires a comprehensive understanding of the mechanisms enabling transitions to sustainable and resilient urban water systems, as well as the development of models and methodologies to guide the transition toward net-zero water communities. To achieve this, the dissertation first aims to deepen the understanding of factors influencing transitions towards sustainable urban water management. This is based on a series of expert interviews conducted with different utilities across North America. The qualitative data analysis provides valuable insights into the complex context of urban water management. The results revealed that achieving social and environmental justice is a prominent driver for utilities to initiate their transition, followed by concerns about climate change, water quality impairments, groundwater depletion, and population growth. Further investigations identified several barriers to the One Water transition. These barriers are not merely financial and technical but also stem from a lack of regulatory frameworks, insufficient community support, and institutional obstacles. Therefore, institutional and regulatory solutions are needed more than technological innovations to support this paradigm shift. Our findings also emphasized the importance of cultural change and the necessity of fostering a One Water mindset among stakeholders at all levels. Additionally, feedback from the participants contributed to a more comprehensive and inclusive definition of One Water. Second, a municipal water demand model was developed using the Integrated Urban Water Model (IUWM) to understand urban water use patterns and influencing factors across urban areas within the Contiguous United States (CONUS). Municipal water use data from 99 cities across the U.S. from 2005 to 2017 was used to calibrate and regionalize model parameters for urban regions across the CONUS. The results identified key factors influencing the regionalization of water model parameters, including "July vapor pressure deficit," "number of employees in other services (except public administration)," and "July precipitation." The study reveals that predictive water use and related uncertainty vary across ecohydrological regions within the CONUS. This variation is significantly influenced by climatic and socio-economic factors, with arid and southern cities showing the highest uncertainty. While densely populated areas exhibit more predictable patterns, small cities demonstrate the highest level of uncertainty in water use projections, primarily due to a higher share of single-family homes and increased outdoor water consumption compared to larger cities. Third, the developed IUWM model was used to estimate municipal water demand across urban areas within the CONUS for the period of 2035-2065 under different future climate and land use scenarios. The results indicated that population growth and land use change are primary drivers of urban water demand. While there are minor annual fluctuations reflecting the effects of different climate scenarios, the hot climate model presents the worst-case scenario, with the lowest reduction in water use intensity and the highest increase in water demand. In this scenario, the average water use demand is projected to increase by 52%, while the average water use intensity (ML/sq.km) will fall by 10%. The projected changes in water use are highly variable across the CONUS, with significant increases expected in urban areas located in the West and Northwest (e.g., Washington and California), Southwest (e.g., Arizona, Utah, Colorado, and New Mexico), Midwest (e.g., Michigan and Wisconsin), and Great Lakes region (e.g., New York and Pennsylvania). Our findings suggest that projections of future municipal water demand are surrounded by considerable uncertainties, particularly in cities located in arid and tropical regions. Furthermore, the results show that while increased urban density typically reduces water use intensity in most areas, increases are expected in parts of the Midwest, Northeast, and West. These trends suggest that once cities reach certain development thresholds (around 50% developed area), densification may no longer effectively reduce municipal water demand, leading to increased indoor and CII (commercial, industrial, and institutional) water consumption, thereby undermining the expected benefits. This highlights the need for effective mitigation strategies, such as demand management and the use of alternative water sources, alongside higher-density development policies to ensure sustainable urban water management in the future. Overall, this dissertation provides a comprehensive understanding of urban water demand in the United States, aiming to achieve sustainable urban water management. The insights gained from this study highlight the importance of integrating land use and water management and fostering collaboration among all stakeholders to achieve the One Water paradigm shift. The results will benefit urban planners and water managers, helping them develop effective strategies to mitigate adverse effects and ensure sustainable water resources for the future.